Early onset primary torsion dystonia with DYT1 positive in an 8-Year-old child: a case report - Naher, Nurun; Begum, Noorjahan; Bhuiyan, Sarwar Jahan (BIRDEM Medical Journal, 2024)
Apart from tremor, primary clinical symptom of primary torsion dystonia (PTD) is dystonia. No history or evidence of neuronal degeneration or acquired origin are present. Out of the seven different loci reported for PTD, only two genes have been identified. This case is being presented with a diagnosis of PTD. The patient, an 8-year-old boy from non-consanguineous parents, had problem in walking for one year, mostly in his left leg and had trouble using his left hand to pick up objects. He had dystonia in the left upper and lower limbs, had intact sensory function with intact cranial nerve function. All his laboratory tests were normal including brain imaging; nevertheless, genetic testing revealed DYT1 was positive. BIRDEM Med J 2024; 14(3): 158-160